Analisis Tingkat Keterampilan Teknik Dasar Futsal pada Siswa Ekstrakulikuler Futsal SMA Negeri 2 Blora (Survei pada Peserta Ekstrakulikuler Futsal SMA Negeri 2 Blora) - Dhani, Dwiki Rachmad; Indarto, Pungki; Warthadi, Anugrah Nur (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2024)
This research aimed to determine the level of basic skills in playing futsal among students at SMA Negeri 2 Blora. The method used is a survey with test and measurement techniques. Objective data will be obtained through tests and measurements. The research subjects were extracurricular students at SMA Negeri 2 Blora, totaling 20 students. Data collection is carried out through observation and tests. Data analysis was carried out descriptively and quantitatively. The results of the research were that the level of futsal playing skills of futsal extracurricular students at SMA Negeri 2 Blora in 2024/2025 was declared "quite good" by as many as 15 students (75%). This means that the futsal skill level of the futsal extracurricular participants is at a fairly good level, while the average score of 48.3119 is in the "medium" interval. Furthermore, this can provide considerations for coaches or trainers to improve physical and psychological quality, develop strategies, techniques, and playing patterns as well as improve the quality and psychological abilities of futsal extracurricular participants. So that the futsal playing abilities and skills of extracurricular futsal students at SMA Negeri 2 Blora in 2024/2025 can continue to improve. In conclusion, there has been an increase in basic playing skills among students at SMA Negeri 2 Blora. Keyword: Ball, Basic Skills; Futsal